New twinlike models for scalar fields. (26th August 2020) - Bazeia, D.; Losano, L.; Marques, M. A.; Menezes, R.
Abstract: This work investigates twinlike scalar field models that support kinks with the same energy density and stability. We find the first-order equations compatible with the equations of motion. We use them to calculate the conditions under which they attain the twinlike character. The linear stability is also investigated, and there we show that the addition of extra requirements may lead to the same stability under small fluctuations.